2022
DOI: 10.3390/nu14102122
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Profiling in the Saliva of Obese Pregnant Women

Abstract: Maternal obesity is associated with inflammation and oxidative stress, strongly impacting the intrauterine environment with detrimental consequences for both mother and offspring. The saliva is a non-invasive biofluid reflecting both local and systemic health status. This observational study aimed to profile the epigenetic signature in the saliva of Obese (OB) and Normal-Weight (NW) pregnant women. Sixteen NW and sixteen OB Caucasian women with singleton spontaneous pregnancies were enrolled. microRNAs were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
(93 reference statements)
2
5
0
Order By: Relevance
“…This is in accordance with data recently reported by our group, which showed a significant association between these pathways and salivary miRNAs of obese pregnant women in the third trimester of pregnancy [25]. These findings may be suggestive of a disarranged fatty acid metabolism, as well as an excessive lysine catabolism in obese pregnancies with or without GDM, which were mediated by miRNA epigenetic alterations.…”
Section: Lipids Fatty Acids and Lysine Metabolism Pathwayssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with data recently reported by our group, which showed a significant association between these pathways and salivary miRNAs of obese pregnant women in the third trimester of pregnancy [25]. These findings may be suggestive of a disarranged fatty acid metabolism, as well as an excessive lysine catabolism in obese pregnancies with or without GDM, which were mediated by miRNA epigenetic alterations.…”
Section: Lipids Fatty Acids and Lysine Metabolism Pathwayssupporting
confidence: 93%
“…Indeed, elevated TGF-Beta1 levels were associated with glucose intolerance and increased adiposity in women with a prior history of GDM [50,51]. The same pathway emerged from our previous miTALOS analysis of third trimester saliva of obese pregnant women [25]. Significantly decreased TGF-Beta1 gene methylation levels were also reported, supporting TGF-Beta1 upregulation.…”
Section: Tgf-beta Signalling Pathwaysupporting
confidence: 62%
See 1 more Smart Citation
“…Among these, hsa-miR-505 and hsa-miR-616 were downregulated while hsa-miR-618, hsa-miR-206, hsa-miR-376a, hsa-miR-517c, hsa-miR-133a, hsa-miR-1285, hsa-miR-635, hsa-miR-551b, hsa-miR-548b-5p, hsa-miR-1256, hsa-miR-302c, hsa-miR-184, and hsa-miR-548c-5p were upregulated in obese pregnant women. These miRNAs were found to be associated with the TGF-β signalling pathway, fatty acids biosynthesis/metabolism, lysine degradation, and ECM-receptor interaction pathways through miRNA pathway enrichment analysis indicating the susceptibility of offspring towards metabolic disorder [87]. Zhao et al observed 23 circulatory miRNAs including miR-15b, MiR-31, miR-122, miR-125b, miR-142, miR-130b, and miR-519d that were associated with obesity and weight gain [88].…”
Section: Mirnas Modulated During Maternal Obesitymentioning
confidence: 99%
“…In addition, the mRNA expression of SOCS3 in visceral fat of GDM women increased, and there was no significant difference in promoter methylation [ 53 ]. The methylation level of the SOCS3 promoter region in saliva of obese pregnant women was lower than that of the control group [ 54 ]. The increase of SOCS3 expression leads to the down-regulation of JAK2 pathway and the impairment of STAT3 signal, leading to leptin resistance, obesity and abnormal glucose metabolism [ 41 ] ( Figure 3 ).…”
Section: Adipokinementioning
confidence: 99%